Longevity record of arctic skua (Stercorarius parasiticus) - Elina Mäntylä; Kari Mäntylä; Jukka Nuotio; Kimmo Nuotio; Matti Sillanpää (John Wiley & Sons Ltd, 2022)
The arctic skua (Stercorarius parasiticus) is one of the most long-lived bird species. In 2010, we captured in Finland an adult, female arctic skua which had been ringed as a nestling in 1987. We tagged it also with a color ring. The bird has last been seen in July 2020 at the age of 33 years, making it most likely the oldest known arctic skua of the world. In 2010–2011 the bird carried a light-level measuring geolocator, the data of which revealed that the bird had spent the nonbreeding season in the Canary Current area on the west coast of Africa. Breeding populations of arctic skuas have declined recently especially in British Isles, thus it is useful to get longevity data of this species with a high breeding site fidelity.